Improved Conductivity of Low‐Temperature‐Synthesized Graphene/Cu for CMOS Backend‐of‐Line Interconnect Applications - Peng‐Chi Wang; Yi‐Hsiang Shih; Chih‐Yuan Tseng; Yu‐Jin Liu; Yao‐Hung Huang; Chrong‐Jung Lin; Ya‐Chin King; Wei‐Chen Tu (Advanced Materials Interfaces)
Abstract This study proposes a synthesis strategy of high‐quality graphene films on the copper foil at a temperature of 400 °C throughout the graphene growth process without employing high‐temperature annealing. Through continuous CO2 laser pretreatment of the copper foil, the surface smoothness improves, and the removal of copper particles and copper oxide results in fewer defects on the foil. Therefore, the nucleation density of graphene is reduced, leading to a more uniform and continuous graphene film and showing an outstanding quality of graphene with low defects and low resistivity compared with other groups. After laser treatment, the copper foil's resistivity decreases from 1.71 ×10−8 to 1.51 ×10−8 Ω·m. The graphene‐coated on laser‐treated foil experiences an even more substantial decrease in resistivity, from 1.34 ×10−8 to 1.18 ×10−8 Ω·m, marking a significant 11.94% reduction. Excitingly, the groundbreaking technique is taken to the next level by applying it to fine copper interconnects as narrow as 0.4 µm. The experiments confirm the successful cultivation of graphene on these miniature scales, showing the immense potential of the approach. The proposed approach aligns with the demands of contemporary CMOS backend‐of‐line processes, facilitating the seamless incorporation of graphene in advanced chip technologies.